Implementasi Baca Tulis Al-Qur’an Secara Daring Pada Siswa Kelas III Sekolah Dasar Islam Terpadu Almaka Jakarta - Mufni Amalia; Abdur Rahim; Ahmad Asrof Fitri (Journal on Education, 2023)
The implemetation of this online Qur’an Literacy is motivated by researcher’s interest in teaching and learning activities to read and write the Qur’an which is carried out as learning material in Primary School or Madrasah Ibtidaiyah. The implemetation of this Online Qur’an Literacy with Tilawati method is a learning which is conducted during Covid- 19 pandemic entering the New Normal. Learning activities are made into a blended learning of classroom learning and online learning. This study aim to describe the implementation of online Qur’an literacy learning along with its supporting and inhibiting factors. In this activity, researcher uses a type of field research that is descriptive qualitative by taking the location at Integrated Islamic Primary School, Almaka Jakarta. Data Collection is carried out by observation, interview and documentation techniques. The results of research on the implementation of online Qur’an literacy of the 3rd grade students of Integrated Islamic Primary school Almaka Jakarta shows that Qur’an Literacy using Tilawati method through clasical and individual approach with a reading and listening technique. There are supporting and inhibiting factors in the implementation of the online reading and writing Qur’an. The supporting factor is there are the training every week to increase the teacher’s skills in teaching the Qur’an to his students. One of the inhibiting factors is the effectiveness of time that occurs when learning online. It can be known that the implementation of Qur’an literacy which is carried out during online learning finds different opinions on face to face learning activities in the classroom. In addition, students also understand the purpose of implementing learning to read and write the Qur’an